2016
DOI: 10.1002/cmmi.1681
|View full text |Cite
|
Sign up to set email alerts
|

Fast synthesis and bioconjugation of 68Ga core‐doped extremely small iron oxide nanoparticles for PET/MR imaging

Abstract: Combination of complementary imaging techniques, like hybrid PET/MRI, allows protocols to be developed that exploit the best features of both. In order to get the best of these combinations the use of dual probes is highly desirable. On this sense the combination of biocompatible iron oxide nanoparticles and 68Ga isotope is a powerful development for the new generation of hybrid systems and multimodality approaches. Our objective was the synthesis and application of a chelator-free 68Ga-iron oxide nanotracer w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 35 publications
(36 reference statements)
3
77
0
2
Order By: Relevance
“…Therefore, reported examples of this methodology use microwave-assisted protocols to synthesize the core-doped iron oxide nanoradiotracers. In 2016, our group reported the synthesis of the first example of 68 Ga core-doped coated iron oxide nanoparticles for PET/MR imaging using microwave technology [72]. In a posterior study in 2017, the same approach was followed using citric acid as coating instead of dextran [73].…”
Section: Nanoparticle Core-dopingmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, reported examples of this methodology use microwave-assisted protocols to synthesize the core-doped iron oxide nanoradiotracers. In 2016, our group reported the synthesis of the first example of 68 Ga core-doped coated iron oxide nanoparticles for PET/MR imaging using microwave technology [72]. In a posterior study in 2017, the same approach was followed using citric acid as coating instead of dextran [73].…”
Section: Nanoparticle Core-dopingmentioning
confidence: 99%
“…This drawback has focused research on finding methods for developing IONPs that serve as positive contrast agents for T1-weighted MRI. Studies have demonstrated that the downsizing of IONP core or coating thickness causes a shift on the NP magnetic behavior from superparamagnetic towards paramagnetic, thus creating T1-weighted MRI contrast agents [72,[87][88][89].…”
Section: Iron Oxide Nanoparticles (Ionps)mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, before anatomical changes appear we can detect the formation of disease which is one great advantage over MR imaging. Pellico et al identified that core doping iron oxide particles with 68 gallium, a radioisotope, will make dual modality‐PET/MRI probes 87. NIR Fluorescence Imaging (NIRF) is highly desirable as auto fluorescence by normal tissue is low at that excitation wavelength.…”
Section: Functionalization To Enhance Multimodal Imagingmentioning
confidence: 99%
“…In this work, the authors described a microwave-driven synthesis of IONPs doped with 64 Cu. In this case, the radiolabelling yield was modest (33%) giving a low specific activity [63].…”
Section: Core Labellingmentioning
confidence: 99%